Penilaian Keterampilan Berpikir Tingkat Tinggi pada Pembelajaran Bahasa Indonesia di Sekolah Menengah Pertama - M. Fachmy Achdan Kadir (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. The purpose of this study was to determine the forms and techniques of assessment, as well as thinking skills applied in Class VIII SMP IT Al-Hikmah Maros. The data from this study are descriptive qualitative data sourced from observations and documentation of the assessments that occur in the classroom. The data analysis technique in this study is qualitative data analysis which consists of three paths that occur simultaneously in the form of data reduction, data presentation and data verification. The results of the study are in the form of an assessment of thinking skills in Indonesian language learning, specifically: (1) the forms of assessment applied by the teacher are in the form of assessment, namely the form of multiple choice assessment, form of assessment of content, form of description assessment, form of question and answer assessment, and form of assessment. group assignment, form of individual assignment assessment. There are also forms of assessment that were not found, namely the form of a true false assessment and a form of matching assessment. (2) Second, assessment techniques for Indonesian language learning for class VIII SMP IT Al-Hikmah Maros. The assessment techniques found are written test assessment techniques, oral test assessment techniques, and assignment assessment techniques. There are also assessment techniques that were not found, namely performance appraisal techniques, project appraisal techniques, and portfolio appraisal techniques. (3) the level of thinking in the assessment which is classified based on the cognitive domain so that it is found that the assessment process in Indonesian language learning still tends to the LOTS level.Keywords: thinking ability, form of assessment, assessment technique